Simultaneous improvement of coercivity and saturation magnetization of M-type strontium ferrite by Nd3+-Co2+ unequal co-substitution. Issue 7 (1st April 2023) - Yu, Xiang; Wang, Lichen; Liu, Ruoshui; Zhou, Ningfang; Xu, Zhiyi; Gong, Huayang; Zhao, Tongyun; Sun, Jirong; Hu, Fengxia; Shen, Baogen
Abstract: We synthesized Sr1- x Nd x Fe12- y Co y O19 ( x = 0–0.25, y = 0–0.1) using a conventional ceramic route. The crystal structures were analyzed using X-ray diffraction. With increasing Nd 3+ and Co 2+ contents, lattice constant a increases, while lattice constant c decreases. In terms of magnetic properties, the saturation magnetization and coercivity are simultaneously increased when x = y = 0.1 (equal co-substitution). This is mainly because the bivalent Co 2+ has a smaller magnetic moment and unquenched orbital moments. When substitution amount x is further increased (unequal co-substitution), the magnetic properties are further improved and reach the optimum values of M s = 76.4 emu/g and H c = 5115 Oe owing to the occupation of the 2 a site by divalent Fe 2+ . The occupancies of Co 2+ and Fe 2+ are further verified using Raman spectroscopy.